Bi-doped Sb2S3 for low effective mass and optimized optical properties. Issue 22 (9th May 2016) - Shang, Ming-Hui; Zhang, Jing; Wei, Shihao; Zhu, Yuejin; Wang, Lin; Hou, Huilin; Wu, Yulian; Fujikawa, Takashi; Ueno, Nobuo
Abstract : Optical properties of Sb2 S3 compounds can be significantly optimized by Bi-incorporation with appropriate density. Abstract : Crystal structures, electronic and optical properties of antimony sulfide (Sb2 S3 ) doped by Bi substituting Sb were calculated using a first-principles approach. The effective masses of electrons and holes can be reduced via site-dependent Bi-incorporation, leading to variation of the band dispersion by tuning chemical bond lengths and bond angles. 1.25 at% Bi-doped Sb2 S3 shows the optimized optical properties. These theoretical results are in good agreement with experimental observations.